2020
DOI: 10.2196/17658
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive App That Improves Tuberculosis Treatment Management Through Video-Observed Therapy: Usability Study

Abstract: Background Treatment of pulmonary tuberculosis (TB) requires at least six months and is compromised by poor adherence. In the directly observed therapy (DOT) scheme recommended by the World Health Organization, the patient is directly observed taking their medications at a health post. An alternative to DOT is video-observed therapy (VOT), in which the patients take videos of themselves taking the medication and the video is uploaded into the app and reviewed by a health care worker. We developed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
(23 reference statements)
1
37
0
Order By: Relevance
“…There were mixed perceptions about the impact of VDOT on privacy and confidentiality, particularly with unintended disease closure, potentially resulting in stigma. Similar perceptions of structural and privacy- and patient-related barriers to VDOT implementation have been previously reported [ 24 , 36 , 37 ]. For example, some studies have reported that video recordings and repeated text reminders are perceived as being overly intrusive [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 75%
“…There were mixed perceptions about the impact of VDOT on privacy and confidentiality, particularly with unintended disease closure, potentially resulting in stigma. Similar perceptions of structural and privacy- and patient-related barriers to VDOT implementation have been previously reported [ 24 , 36 , 37 ]. For example, some studies have reported that video recordings and repeated text reminders are perceived as being overly intrusive [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 75%
“…While many rapid pathogen detection technologies have undergone validity analyses, there is a literature gap of usability analyses for such technologies [14][15][16][17][18]. Many usability studies instead evaluate technologies that aid interventions such as behavioral change, treatment adherence, or clinical decision making [23][24][25][26]. Thus, this study can serve as a model of iterative convergent mixed methods research design for device development to further promote usability analysis of rapid pathogen detection technologies and produce rapid detection devices that better fit into user workflows for increased uptake.…”
Section: Principal Findingsmentioning
confidence: 99%
“…While the field of mHealth and rapid diagnostic testing for infectious disease is fast-growing, few rapid pathogen detection technologies have been developed for environmental surveillance [12,22]. Moreover, many mHealth usability studies have evaluated interventions such as behavioral change, medication adherence, or clinical decision-making technologies, but there is a literature gap for usability studies evaluating rapid pathogen detection technology [23][24][25][26]. By providing input in the device development process, end users can become cocreators and feel ownership in the device design, enabling greater uptake and integration into workflows.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the long process of treatment in patients with TB, the need for treatment adherence especially when the initial signs of improvement appear, and information about the continued use and consequences of arbitrary discontinuation of the drug, customized messages are sent to patients according to the treatment schedule (54). In addition, to achieve better results and measure the actual effectiveness of the program, evaluation of the program by patients with TB is recommended, which requires shortterm education of patients and the inclusion of the needs of such users.…”
Section: Clinical Implications: Mobile Self-care System For Tuberculosis Controlmentioning
confidence: 99%